Characterization of Pathogenic Vibrio parahaemolyticus from the Chesapeake Bay, Maryland - Chen, Arlene J.; Hasan, Nur A.; Haley, Bradd J.; Taviani, Elisa; Tarnowski, Mitch; Brohawn, Kathy; Johnson, Crystal N.; Colwell, Rita R.; Huq, Anwar (Frontiers in Microbiology, 2017)
Vibrio parahaemolyticus is the leading cause of bacterial gastroenteritis associated with seafood consumption in the United States. Here we investigated the presence of virulence factors and genetic diversity of V. parahaemolyticus isolated from water, oyster, and sediment samples from the Chesapeake Bay, Maryland. Of more than 2,350 presumptive Vibrio collected, more than half were confirmed through PCR as V. parahaemolyticus, with ten encoding both tdh and trh and six encoding only trh. Potentially pathogenic V. parahaemolyticus were then serotyped with O1:KUT and O3:KUT predominant. Furthermore, PFGE was performed and the constructed dendrogram displayed high diversity, as did results from multiple-locus VNTR analysis. Vibrio parahaemolyticus was readily isolated from Chesapeake Bay waters but was less frequently isolated from oyster and sediment samples collected during this study. Potentially pathogenic V. parahaemolyticus was isolated in fewer numbers and the isolates displayed expansive diversity. Although characteristics of the pathogenic V. parahaemolyticus were highly variable and the percent of pathogenic V. parahaemolyticus detected was low, it is important to note that, pathogenic V. parahaemolyticus are present in the Chesapeake Bay, warranting seafood monitoring to minimize risk of disease for the public, and to reduce the economic burden of V. parahaemolyticus related illness.